2004
DOI: 10.1097/01.ju.0000140957.31325.7f
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting Preferences for Drug Treatment of Lower Urinary Tract Symptoms Associated With Benign Prostatic Hyperplasia

Abstract: Given the attribute levels of BPH medical treatment, overall community dwelling men preferred the 5alpha-reductase inhibitor over alpha-blockers. In the interests of shared decision making it is important to consider the importance of eliciting the preferences of patients with BPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 11 publications
4
61
0
Order By: Relevance
“…They include watchful waiting, medical therapy with α-blockers or 5 α-reductase inhibitors, hormone therapy, surgery and phytotherapy (Watson et al, 2004;Kaplan, 2006). The use of complementary and alternative medicine (CAM) for the treatment of BPH is becoming popular.…”
Section: Introductionmentioning
confidence: 99%
“…They include watchful waiting, medical therapy with α-blockers or 5 α-reductase inhibitors, hormone therapy, surgery and phytotherapy (Watson et al, 2004;Kaplan, 2006). The use of complementary and alternative medicine (CAM) for the treatment of BPH is becoming popular.…”
Section: Introductionmentioning
confidence: 99%
“…In health economics, the number of DCE studies has sharply increased during the past decade [8][9][10][11][12]. More specifically, many DCE applications have aimed to evaluate the health and non-health dimensions of medical treatments, for example: miscarriage management [13]; varicella vaccination [14]; insulin mixtures [15]; alcoholism medication [16]; colorectal cancer screening [17]; weight loss programmes [18]; knee injuries detection [19]; and lower urinary tract symptoms [20]. In Table 1, we provide a nonexhaustive list of empirical papers using DCE to value medical interventions along with the dimensions that were assessed.…”
Section: Related Workmentioning
confidence: 99%
“…Roux et al [18] Weight loss programmes Programme cost, travel time to programme, amount of doctor involvement, programme components emphasised, focus of programme Bryan et al [19] Knee injury detection % chance of requiring arthroscopy, time from initial consultation to end of treatment, % chance that knee problem is completely resolved, total cost to the patient Watson et al [20] Lower urinary tract symptoms Time to symptom improvement, treatment decreases prostate size, sexual side effects of treatment, nonsexual side effects of treatment, treatment cost, % chance of surgery abstinence is negatively related to withdrawal symptoms. The medication precisely increases the success rate by decreasing these withdrawal symptoms.…”
Section: Framework For Analysismentioning
confidence: 99%
“…The attributes of a 5ARI (dutasteride) and alfa blockers were investigated in a discrete choice study in community dwelling men (>40 years) in the UK (Watson et al 2004). Using willingness to pay as a measure of preference for the defined drug profiles, respondents were worse off (by almost £12 monthly) if they received alfa blockers compared with no medication.…”
Section: Medical Therapymentioning
confidence: 99%
“…showed that the respondents were willing to wait 13, 2, and 8 months longer for symptom improvement in exchange for reduced prostate size, and an absolute 1% decrease in the risks of AUR and surgery, respectively (Watson et al 2004). …”
Section: Table 1 | Evidence Base Included In the Reviewmentioning
confidence: 99%